Diurnal Variation in Canopy Temperature and Stress Degree Day Index of Mungbean (Vigna radiata) Varieties under Different Dates of Sowing - Tzudir, L.; Bera, P. S.; Chakraborty, P. K. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted in the summer seasons of 2010 and 2011 on four mungbean varieties (V1 -Pant Mung-5, V2-Bireswar, V3-RMG-62 and V4-Sukumar) sown on three different dates (D1-15th February, D2 -1st March and D3-15th March) at the university research farm under Sub-humid tropical environment. The experiment was laid out in a split plot design where the sowing dates and the varieties were considered as main plot and sub plot treatments respectively. The objective of this study was to identify the stress period in mungbean crop through canopy temperature measurement. The canopy temperatures were measured at 7:30, 11:30 and 15:30 hour during 25 to 46 days after emergence (DAE) at seven days interval. Canopy temperature increased from 7:30 to 11:30 hr, followed by a decline at 15:30 hr with a few aberrations. The mean canopy temperature under D2 was lower than D1 and D3 in both the year which indicated no moisture stress suffered by the crop during that period. The SDDI was more at 11.30 hr which indicated moisture stress at that period. Overall, the moisture adequacy was better under D2 sowing giving the probability of good yield under this sowing and was closely followed by D3 sown crops. The variety V1 suffered less moisture stress in comparison to the other varieties.